Studi Timbulan Sampah Domestik Di Kabupaten Rokan Hilir (Studi Kasus Di Wilayah Kecamatan Pasir Limau Kapas) - Witami, Witami; Yenie, Elvi; Priyambada, Gunadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Kecamatan Pasir Limau Kapas is an area located at the coast of Rokan Hilir Regency with an area of 1,206.72 km2. It consists of one Kelurahan and 7 Kepenghuluan with a total population of 40,140 people and the Head of Family (KK) 9,718. The types of house buildings in this area are categorized into three types, namely permanent type 414 units, semi-permanent 148 units and non-permanent 10912 units. The number of samples of domestic waste from the type of permanent housing is 5 units, semi-permanent 5 units and non-permanent 19 units. This research was conducted based on the SNI 19-3964-1994 method for eight consecutive days. The average waste generation obtained was from the permanent type (weight 0.276 kg/o/h and volume 2.817 l/o/h), semi-permanent (weight 0.256 kg/o/h and volume 4.040 l/o/h) and non-permanent (weight 0.126 kg/o/h and volume 1.482 l/o/h) with a total domestic waste generation of 7658.196 kg/h. Keywords: Waste pile